The Role of Islamic Service Quality on Intention to Use Indonesian Islamic Bank: Trust as an Intervening Variable - Saputra, Moch Adika; Rahmawaty, Anita (MALIA: Journal of Islamic Banking and Finance, 2023)
This study aims to determine the effect of Islamic Service Quality on Intention to Use at Indonesian Islamic Bank with Trust as an Intervening Variable. Type of Field Research research with a sample of 235 respondents. The sampling method uses Non-Probability Sampling with Acidental Sampling technique. The data from this study were analyzed using the Structural Equation Modeling (SEM) method based on the Partial Least Square (PLS) Second Order model with an Embedded Two-Stage Approach. The results of this study show that: (1) Islamic Service Quality has a positive and significant effect on Intention to Use at Indonesian Islamic Bank. (2) Islamic Service Quality has a positive and significant effect on Trust at Indonesian Islamic Bank. (3) Trust has a positive and significant effect on Intention to Use at Indonesian Islamic Bank. (4) Trust can mediate Islamic Service Quality on Intention to Use at Indonesian Islamic Bank by having influence in Partial Mediation.Keywords: Islamic Service Quality, Trust, Intention to Use